Implementation of an intensified outpatient follow-up protocol improves outcomes in patients with ventricular assist devices - Hamed, Sonja; Schmack, Bastian; Ehlermann, Philipp; Ruhparwar, Arjang; Katus, Hugo; Raake, Philip; Kreußer, Michael (Clinical research in cardiology, 2019)
Background: Ventricular assist devices (VAD) are increasingly used as long-term treatment for advanced heart failure. However, survival after VAD implantation is still unsatisfactory, and no specific outpatient follow-up algorithms have been formally established. Here, we evaluate the effect of an intensified follow-up protocol (IFUP) on survival rates and VAD-associated complications. Methods and results: This is a retrospective study of 57 patients who received a VAD at our center between February 2013 and December 2017. Inclusion criteria were discharge home after VAD implantation and follow-up in our VAD outpatient clinic. Patients implanted after October 2015 (n = 30) were monitored according to IFUP. This protocol embodied formalized, multi-disciplinary clinical visits every 4-8 weeks including a cardiologist, a cardiothoracic surgeon and a VAD-coordinator and was characterized by optimized anticoagulation and wound management as well as guideline-directed medical therapy. One-year survival in the IFUP patients was 97%, compared to 74% in the pre-IFUP era (p = 0.01). Implementation of IFUP was associated with a 90% risk-reduction for 1-year mortality (relative risk 0.099; p = 0.048). The rate of complications, e.g., device thrombosis and major bleeding, was significantly reduced, resulting in superior event-free survival in the IFUP group (p = 0.003). Furthermore, by implementation of IFUP, a more stable anticoagulation adjustment was achieved as well as an improved adherence to guideline-directed medical therapy. Conclusion: Implementation of an IFUP for VAD patients is associated with a significant decrease in 1-year all-cause mortality. This emphasizes the need for more vigilance in the management of VAD patients by a dedicated multi-disciplinary team.
Gesehen am 11.11.2019